In hoc signo vince! - Watson, Carl; Gutleben, Max von 1953-; Rauchenberger, Johannes 1969-; Raboteau, Emily; Arnautović, Ljuba 1954-; Halbrainer, Heimo 1963-; Stoeckl, Kristina 1977-; Berton, Benjamin 1974-; Danzer, Gudrun 1958- (Verlag für moderne Kunst, 2024)
It contains texts that thematically deal with the unholy alliance of politics and religion. With a foreword by Karin Buol-Wischenau and Katia Huemer, as well as essays and poems by Carl Watson, Elias Schneitter, Johannes Rauchenberger, Emily Raboteau, Ljuba Arnautovic, Heimo Halbrainer, Kristina Stoeckl, Benjamin Berton, and a conversation between Gudrun Danzer and Hannes Priesch
Keywords: Priesch, Hannes -- 1954-; Hannes Priesch; Katia Huemer; Kunst und Welt; Aufsatzsammlung